Differential Information Economies - Glycopantis, Dionysius; Yannelis, Nicholas C. (Studies in Economic Theory, 2005)
One of the main problems in current economic theory is to write contracts which are Pareto optimal, incentive compatible, and also implementable as a perfect Bayesian equilibrium of a dynamic, noncooperative game. The question arises whether it is possible to provide Walrasian type or cooperative equilibrium concepts which have these properties. This volume contains original contributions on noncooperative and cooperative equilibrium notions in economies with differential information and provides answers to the above questions. Moreover, issues of stability, learning and continuity of alternative equilibria are also examined. .